Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Pengiriman Peserta Magang Ke Jepang Pada Dinas Tenaga Kerja Kota Medan Dengan Metode Analytical Hierarchy Process (AHP) - Ryki Perdana; Achmad Yani (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Selection of apprentices to Japan is an activity that is often done by the Medan City Manpower Office to find apprentices to Japan who are eligible to be sent and placed there. Every agency or company in general has used a computerized application to process data easily and quickly. The reality on the ground is that the Medan City Manpower Office is not ready in the process of selecting apprentices to Japan. The system used is still manual, resulting in a lack of effectiveness in selecting apprentices to Japan. The use of computers is very necessary for data processing so as to produce an accurate and fast information. Computerized data processing is needed to obtain information that can be used to produce solutions to existing problems. To solve the problems above, we need a Decision Support System. Decision support system is a system that helps the performance of staff recruiting at the Medan City Manpower Office. For this reason a Decision Support System to determine the appropriateness of apprentices to Japan. This study applies the Analytical Hierarchy Process (AHP) method which is one that can solve multi-criteria problems. The benefit of this research is to provide a more effective and efficient alternative to facilitate decision making in determining the appropriateness of apprentices to Japan. Inputs requested from the user are the assessment criteria and the results provided by the system are alternative apprenticeship data based on the highest priority order of alternative values.Keywords: Decision Support System, AHP, Internship Participant Eligibility